2020
DOI: 10.3390/ph13110383
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Solid Dispersions Composed of Curcumin, Hydroxypropyl Cellulose and/or Sodium Dodecyl Sulfate by Grinding with Vibrational Ball Milling

Abstract: Solubility is an important physicochemical property affecting drug bioavailability. One approach to improve drug solubility is using amorphous formulations, which can improve solubility by up to a 1000-fold. Herein, amorphous curcumin (CUR) and amorphous solid dispersions (SDs) consisting of CUR, hydroxypropyl cellulose (HPC) and/or sodium dodecyl sulfate (SDS) were developed using vibrational ball milling. The resulting ground mixtures (GMs) were characterized using powder X-ray diffractometry, Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The amorphous state of polyphenols is most often stabilized by hydrogen bonds. Recent work shows the amorphous solid dispersion of such polyphenols as quercetin [11,16,17], resveratrol [18], curcumin [18][19][20], naringenin [21], daidzein [22], and genistein [23]. The amorphous form of pterostilbene was obtained, for example, by Tzeng et al via nanoprecipitation with Eudragit ® e100 and polyvinyl alcohol (PVA) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous state of polyphenols is most often stabilized by hydrogen bonds. Recent work shows the amorphous solid dispersion of such polyphenols as quercetin [11,16,17], resveratrol [18], curcumin [18][19][20], naringenin [21], daidzein [22], and genistein [23]. The amorphous form of pterostilbene was obtained, for example, by Tzeng et al via nanoprecipitation with Eudragit ® e100 and polyvinyl alcohol (PVA) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the ball milling method was also reported by Mai et al [47], using Hydroxypropyl Cellulose (HPC) and Sodium Dodecyl Sulfate (SDS) as carriers. The results showed that with an increase in HPC, the solubility of curcumin also increased.…”
Section: Co-milling Methodsmentioning
confidence: 95%
“…The mechanism underlying increased solubility involves the hydrophilic carrier enhancing the drug dissolution rate by reducing crystal size and particle porosity. Solid dispersions are categorized into eutectic systems, glass solutions, suspensions, and solid solutions based on molecular arrangement ( Malkawi et al, 2022 ; van Hoogevest, 2017 ; Mai et al, 2020 ). Various technologies, including the hot-melt extrusion method, solvent method, electro-spinning, and spray drying, have been employed for solid dispersion preparation ( Williams et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%